Temporal characteristics of the human mirror neuron system. Research using transcranial magnetic stimulation - K. Nieto-Doval; A. A. Ragimova; A. O. Vyazmin; O. I. Shevtsov; M. Feurra (Нервно-мышечные болезни, 2024)
Background. Mirror neurons (MN) are integral to linking the perception of actions with their execution, activating during both action observation and execution. While extensive research has elucidated their functional roles, the temporal dynamics of MN responses in humans remain insufficiently understood.Aim. To investigate the temporal profile of MN activity during hand movement observation using transcranial magnetic stimulation at at different time intervals (0, 320, 640, 1000, 1320, 1640 ms from the beginning of the demonstrated movement, time ranges from 1000 to 1640 ms correspond to the time interval after the end of the movement).Materials and methods. Twenty right-handed participants underwent neuronavigated transcranial magnetic stimulation targeting the left primary motor cortex during the observation of hand movements. Motor evoked potentials were recorded from the first dorsal interosseous and abductor digiti minimi muscles at various time points relative to movement onset.Results. A three-way interaction between movement type, muscle, and time was observed. Muscle-specific responses and intermuscular differences became prominent at 640 ms, extending into post-movement periods (1000, 1320, 1640 ms). Notably, excitatory responses were seen in muscles corresponding to the observed action, while unrelated muscles exhibited inhibitory patterns, intensifying over time.Conclusion. These findings reveal a complex excitatory-inhibitory interplay in the MN system, resembling motor surround inhibition. The extended temporal activity of MN suggests their role in processing action completion and potential outcomes. This study provides novel insights into MN dynamics and underscores the relevance of these mechanisms for motor rehabilitation strategies. Further research is required to explore MN activity at extended time points.